2022
DOI: 10.1177/20552173221109771
|View full text |Cite
|
Sign up to set email alerts
|

Trans-anal irrigation in patients with multiple sclerosis: Efficacy in treating disease-related bowel dysfunctions and impact on the gut microbiota: A monocentric prospective study

Abstract: Background Constipation and faecal incontinence are not so uncommon in patients with multiple sclerosis, impairing quality of life. The gut microbiota is altered in multiple sclerosis patients and likely contributes to disease pathogenesis. Trans-anal irrigation has been proven to allow treatment of neurogenic bowel dysfunction and may affect gut microbiota. Objectives The primary outcome was trans-anal irrigation effectiveness on constipation and faecal incontinence. The secondary outcome was gut microbiota p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Research regarding NBD within patients with MS is likewise scant. Recommendations are usually based on results from patients within the SCI group or idiopathic bowel symptoms, leaving clinicians with the above-mentioned limitations and the lack of a formalized approach regarding bowel symptoms [1,2,16,19,26,28,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research regarding NBD within patients with MS is likewise scant. Recommendations are usually based on results from patients within the SCI group or idiopathic bowel symptoms, leaving clinicians with the above-mentioned limitations and the lack of a formalized approach regarding bowel symptoms [1,2,16,19,26,28,53].…”
Section: Discussionmentioning
confidence: 99%
“…Within the MS population, several studies concluded that TAI improved bowel symptoms and quality of life in persons with NBD [5,53,54]. Amongst MS patients, one study found that the sole predictive factor for successful treatment was impaired anal electrosensitivity at baseline [5].…”
Section: Transanal Irrigationmentioning
confidence: 99%
“…In another study, Ascanelli et al studied the effects of TAI on FI and constipation in MS individuals [ 69 ]. Quality of life and NBD scores both improved after using TAI for these patients.…”
Section: The Role Of Tai In Managing Nbdmentioning
confidence: 99%
“…When pressurized water is introduced via the inflated rectal balloon catheter, it stretches the luminal wall and activates gut pacemaker cells. The activation of intrinsic neuromuscular mechanisms interferes with the hyper-reflexic bowel, which is characterized by overactive segmental peristalsis In another study, Ascanelli et al studied the effects of TAI on FI and constipation in MS individuals [69]. Quality of life and NBD scores both improved after using TAI for these patients.…”
Section: Proposed Moa Of Tai In Triggering Effective Evacuationmentioning
confidence: 99%